A methodological review of demand analysis: An example of health care services - Adhikari, Shiva Raj (Economic Journal of Development Issues, 2012)
Demand describes the quantity of goods or services per unit of time that an individual purchases and consumes given the set of the prices and income of the consumer. The demand models based on continuous choice or discrete choice are popular in the economic literatures. Discrete choice depicts where and what kinds of health services to consume while the continuous choice portrays how much of health services to consume. Specification of the behavioural model and estimation of the parameters of the model that are interrelated tasks in discrete choice model are challenging for the researchers. Health sector data have special features like discrete nature of the data, problems of censoring, integer counts or time duration and several factors complicate attempts to obtain unbiased estimates of the impact of variables that influence demand for health care. The health care data provide wider applications of econometrics models. These models have some advantages in presenting and analyzing the choice behaviour; however, they have some limitations as well. Subsequently, the researchers are continuously interested to find and to apply appropriate models to describe the choice behaviour of the decision makers. DOI: http://dx.doi.org/10.3126/ejdi.v13i0.7215 Economic Journal of Development Issues Vol.13 & 14 2011, pp.119-130